A Review of the CRISPR-Cas System: Mechanism, Applications, and Future Perspectives - Manjula A C; Dr Shubha; Prathibha K Y; Marhoob Banu (The Bioscan, 2025)
The CRISPR-Cas system has revolutionized molecular biology as a powerful genome editing tool derived from a natural bacterial immune mechanism. This review explores the biological mechanism of CRISPR-Cas systems, particularly the widely used CRISPR-Cas9, along with other Cas variants. Emphasis is placed on its development as a genome-editing platform, its wide-ranging applications in medicine, agriculture, and biotechnology, and the associated ethical and technical challenges. Advances in CRISPR technologies promise unprecedented capabilities in treating genetic disorders, enhancing crop traits, and engineering synthetic organisms. However, concerns over off-target effects, gene drives, and germline editing warrant careful regulatory oversight. This review provides a comprehensive overview of the CRISPR-Cas system and highlights future directions in this rapidly evolving field.